SENIOR–LØKEN SYNDROME: A Case Series and Review of the Renoretinal Phenotype and Advances of Molecular Diagnosis. Issue 10 (October 2021) - Yahalom, Claudia; Volovelsky, Oded; Macarov, Michal; Altalbishi, Alaa; Alsweiti, Yahya; Schneider, Nina; Hanany, Mor; Khan, Muhammad Imran; Cremers, Frans P.M.; Anteby, Irene; Banin, Eyal; Sharon, Dror; et al.
Abstract : Purpose: To report genetic and clinical findings in a case series of 10 patients from eight unrelated families diagnosed with Senior–Løken syndrome. Methods: A retrospective study of patients with Senior–Løken syndrome. Data collected included clinical findings electroretinography and ocular imaging. Genetic analysis was based on molecular inversion probes, whole-exome sequencing (WES), and Sanger sequencing. Results: All patients who underwent electrophysiology (8/10) had widespread photoreceptor degeneration. Genetic analysis revealed two mutations in NPHP1, two mutations in NPHP4, and two mutations in IQCB1 ( NPHP5 ). Five of the six mutations identified in the current study were found in a single family each in our cohort. The IQCB1 -p.R461* mutation has been identified in 3 families. Patients harboring mutations in IQCB1 were diagnosed with Leber congenital amaurosis, while patients with NPHP4 and NPHP1 mutations showed early and sector retinitis pigmentosa, respectively. Full-field electroretinography was extinct for 6 of 10 patients, moderately decreased for two, and unavailable for another 2 subjects. Renal involvement was evident in 7/10 patients at the time of diagnosis. Kidney function was normal (based on serum creatinine) in patients younger than 10 years. Mutations in IQCB1 were associated with high hypermetropia, whereas mutations in NPHP4 were associated with high myopia. Conclusion: Patients presenting with infantile inherited retinal degeneration are not universally screened for renal dysfunction. Modern genetic tests can provide molecular diagnosis at an early age and therefore facilitate early diagnosis of renal disease with recommended periodic screening beyond childhood and family planning. Abstract : Molecular tests facilitate early diagnosis of inherited retinal degeneration and improve the development of personalized medicine.